Small mine size is associated with lung function abnormality and pneumoconiosis among underground coal miners in Kentucky, Virginia and West Virginia. Issue 10 (22nd July 2014) - Blackley, David J; Halldin, Cara N; Wang, Mei Lin; Laney, A Scott
Abstract : Objectives: To describe the prevalence of lung function abnormality and coal workers' pneumoconiosis (CWP) by mine size among underground coal miners in Kentucky, Virginia and West Virginia. Methods: During 2005–2012, 4491 miners completed spirometry and chest radiography as part of a health surveillance programme. Spirometry was interpreted according to American Thoracic Society and European Respiratory Society guidelines, and radiography per International Labour Office standards. Prevalence ratios (PR) were calculated for abnormal spirometry (obstructive, restrictive or mixed pattern using lower limits of normal derived from National Health and Nutrition Examination Survey (NHANES) III) and CWP among workers from small mines (≤50 miners) compared with those from large mines. Results: Among 3771 eligible miners, those from small mines were more likely to have abnormal spirometry (18.5% vs 13.8%, p<0.01), CWP (10.8% vs 5.2%, p<0.01) and progressive massive fibrosis (2.4% vs 1.1%, p<0.01). In regression analysis, working in a small mine was associated with 37% higher prevalence of abnormal spirometry (PR 1.37, 95% CI 1.16 to 1.61) and 2.1 times higher prevalence of CWP (95% CI 1.68 to 2.70). Conclusions: More than one in four of these miners had evidence of CWP, abnormal lung function or both. Although 96% of miners in the study have worked exclusively under dust regulations implemented following the 1969 Federal Coal Mine Safety and Health Act, we observed high rates of respiratory disease including severe cases. The current approach to dust control and provision of safe work conditions for central Appalachian underground coal miners is not adequate to protect them from adverse respiratory health effects.